2020
DOI: 10.1177/1073274820922553
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib Combined With Radiotherapy Enhances Antitumor Effects in an In Vivo Nasopharyngeal Carcinoma Model

Abstract: Vascular endothelial growth factor (VEGF) and its receptor (VEGFR) are highly expressed in nasopharyngeal carcinoma; therefore, blocking the binding of VEGF and VEGFR may be a potential way to treat nasopharyngeal carcinoma. Apatinib inhibits tumor angiogenesis. Previous studies have suggested that treatment with apatinib has an antitumor effect on nasopharyngeal carcinoma. This study will investigate the effect of apatinib combined with radiotherapy. In this study, nude mice injected with CNE-2 nasopharyngeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…14 Currently, the main molecularly targeted therapeutic drugs with proven efficacy in the treatment of NPC are epidermal growth factor receptor (OMIM: 131550) inhibitors and vascular endothelial growth factor inhibitors. 15,16 Previous studies have demonstrated the clinical efficacy and good safety of molecular targeted therapy in NPC. However, many studies are only in the preclinical or early research stage, 17 and more phase III clinical trials are needed.…”
Section: Discussionmentioning
confidence: 99%
“…14 Currently, the main molecularly targeted therapeutic drugs with proven efficacy in the treatment of NPC are epidermal growth factor receptor (OMIM: 131550) inhibitors and vascular endothelial growth factor inhibitors. 15,16 Previous studies have demonstrated the clinical efficacy and good safety of molecular targeted therapy in NPC. However, many studies are only in the preclinical or early research stage, 17 and more phase III clinical trials are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy combined with anti-angiogenesis therapy has been proved to be a good way to improve the anti-tumor effect in many types of cancer. Liu et al (Liu et al 2020) evaluated the therapeutic effect of radiotherapy combined with apatinib (anti-angiogenesis drug) on mouse nasopharyngeal carcinoma xenograft model, and found that the tumor inhibition effect of combined therapy was stronger than that of apatinib alone or radiotherapy alone. This is similar to the research results of Koo et al (Koo et al 2016) and Gao et al (Gao et al 2015), which all indicate the synergistic effect of anti-angiogenesis therapy on radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…All human experiments were approved by the Ethics Committee of the First Affiliated Hospital of Soochow University, China. On the seventh day after glioma cell inoculation, the mice that survived were intraperitoneally injected with apatinib (200 mg/kg/day) in phosphate-buffered saline (PBS) and saline solution, 4 days/week for 4 weeks [ 54 ]. The fresh drug was used for all doses for both in vitro and in vivo survival experiments.…”
Section: Methodsmentioning
confidence: 99%